Geopolitics from the All-Party Parliamentary Group for the Polar Regions - Estenssoro-Saavedra, J (FLACSO-ECUADOR, 2025)
Introduction: the Antarctic statu quo could change. Academic debates in the Global North criticise China and Russia but rarely question the strategies of their own countries. Therefore, it is necessary to broaden the perspective and promote analysis on the projection of power of the Global North in Antarctica. Objective: Therefore, this research analyses the geopolitics of the British parliamentary group All-Party Parliamentary Group for the Polar Regions (APPG for the Polar Regions) between 2015 and 2024. Methodology: to do so, the analysis is qualitative and based on primary sources, structured in three questions: (1) what role have they attributed to Punta Arenas in the Antarctic context?, (2) how has the group perceived the effects of climate change about Antarctica? and (3) what international actions have they promoted in the region? Conclusions: the results show that climate change is a central issue on the APPG for the Polar Regions agenda, which they use to foster cooperation with Chilean scientists, justify the British presence in Antarctica through science and strengthen collaborations with the United States while disseminating a climate agenda in the Antarctic Parliamentary Assemblies.